Ustilaginoidin M1, a new bis-naphtho-γ-pyrone from the fungus Villosiclava virens. Issue 9 (3rd May 2021) - Meng, Jiajia; Zhao, Siji; Dang, Pengqin; Zhou, Zhiyao; Lai, Daowan; Zhou, Ligang
Abstract: Ustilaginoidin M1 (1 ), a novel bis-naphtho-γ-pyrone, was isolated from the cultures of the fungus Villosiclava virens which was the pathogen of rice false smut disease. Its structure was elucidated by spectroscopic analysis and by comparison of its physical and spectroscopic data with the literature. Compound 1 was tested for its cytotoxicity against five human cancer cell lines. Abstract :